Resin-based composite reinforced sealant - Croll, T. P.; Sundfeld, Renato Herman [UNESP] (Amer Soc Dentistry Child, 1999)
Purpose: To describe and picture a technique for using a resin-bonded sealant reinforced by inclusion of resin-based composite, before polymerization. Method: Using an extracted mandibular molar, embedded in plaster and isolated with a rubber dam, a step-by-step depiction of the technique is shown. Results: A picture of a six-year-old sealant in a first permanent molar, still in perfect condition, is shown. Conclusion: This technique offers a reliable method for treating pits and fissures.
Keywords: resin-bonded sealant; resin-based composite